Accounting and Financial Literacy as Preparation for Work or Continuing Study and Following the MBKM - Diyani, Lucia Ari; Rahman, Huda Aulia; Kurniawan, Surya Hadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service activity is carried out for class 12 high school students. This activity aims to equip students to have competencies, outside of the majors studied at school. This service activity provides three benefits, namely increasing understanding regarding accounting and financial literacy, preparing students to better understand the benefits of the Independent Learning Curriculum (MBKM) when continuing college and providing an overview of the field of work for students who choose to work after graduating from school. Of the 35 participants, 98% of participants said they were very satisfied, and the remaining 2% said they were satisfied. Then the results of the questionnaire regarding the sustainability of the training showed that 100% or all participants wanted further service activities.